Bibliography: Conflict in Syria (Part 5) - Tinnes, Judith (Perspectives on terrorism, 2024)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on the Syrian conflict. To keep up with the rapid changing political events, the most recent publications have been prioritized during the selection process. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text as well as reference retrieval systems have been employed to broaden the search.